Techniques for predicting metal mining influenced water - Williams, R. David 1949-; Diehl, Sharon F. (Management technologies for metal mining influenced water ;, 2014)
Techniques for Predicting Metal Mining Influenced Water is a must-read for planners, regulators, consultants, land managers, researchers, students, stakeholders, and others concerned about mining influenced water. Identifying potential mine wastes and their characteristics, and predicting their drainage quality are critical aspects of mine site design, operations, and closure planning. Failure to effectively conduct these evaluations for a mine site can result in environmental compliance issues that may create long-term financial liabilities. The fifth in a series of six handbooks on tech.